Exploring opportunities and challenges experienced by teachers teaching children with autism spectrum disorder (ASD) in a special school resource centre - Manukwana, Xoliswa (Stellenbosch : Stellenbosch University, 2020)
Thesis (MEdPsych)--Stellenbosch University, 2020.